The Effect of Compensation and Motivation on Performance Employees at Public Works and Spatial Planning Service of North Aceh - Desky, Harjoni (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research explores the intricate relationship between compensation, motivation, and employee performance within the Public Works and Spatial Planning Office of North Aceh Regency. Through a quantitative approach employing multiple and simple linear regression analyses with SPSS, the study investigates the impact of compensation and motivation on employee performance, using a sample of 60 employees selected through random sampling. The findings indicate that both compensation and motivation significantly contribute to heightened employee performance, constituting crucial elements for organizational success. The compensation regression coefficient is 0.569, affirming that increased compensation positively influences employee performance. Similarly, the motivational regression coefficient is 1.022, suggesting that heightened motivation positively impacts employee performance. The study underscores the theoretical significance of recognizing compensation and motivation as pivotal factors in human resource management. Practical implications include the need for well-structured compensation systems and effective motivational strategies to optimize employee performance. Despite these contributions, caution is advised in generalizing findings, and future research could delve into additional factors influencing employee performance for a more comprehensive understanding in the public sector.